The Effects of Anodal Stimulation of the Left Prefrontal Cortex on Sentence Production - Nozari, Nazbanou; Arnold, Jennifer E.; Thompson-Schill, Sharon L. (Brain stimulation, 2014)
Most studies in which Anodal Transcranial Direct Current Stimulation (A-tDCS) has been used to improve language production have focused on single words. Yet sentence production requires more than lexical retrieval. For example, successful suppression of the past and careful planning of the future are two critical requirements for producing a correct sentence. Can A-tDCS improves those, and by extension, production at the sentence level? Given that many aspects of sentence production beyond word retrieval require frontally-mediated operations, we hypothesized that A-tDCS to the left prefrontal cortex should benefit various operation involved in producing sentences, two of which, suppression of the past and planning of the future, were targeted in this study. We used a paradigm that elicited construction of sentences through event description, but was structured enough to allow for between-subject comparison, clear error identification, and implementation of experimental manipulations to probe certain aspects of production. We showed that A-tDCS to the left PFC reliably decreased the number of incomplete and errorful sentences. When the origin of this improvement was probed, we found that A-tDCS significantly decreased errors due to premature commitment to the future word (insufficient internal monitoring), and had a marginal effect on errors of perseverations (insufficient suppression of the past). We conclude that A-tDCS is a promising tool for improving production at the sentence level, and that improvement can be expected when internal monitoring and control over verbal responses is impaired, or for certain cases of perseveratory errors. •We propose the first systematic paradigm for studying effects of tDCS on sentence production.•Anodal tDCS of PFC reliably decreased the rate of omitted and errorful sentences.•A reliable decrease was found for errors due to premature commitment.•A marginal effect was found for perseveratory errors.